MASYARAKAT EKONOMI ASEAN: HARAPAN DAN TANTANGAN BAGAIMANA DAYA SAING INDONESIA DI ASEAN - Wardoyo Wardoyo (Universitas Muhammadiyah Tangerang, 2017)
Asean Economic Community (AEC) was officially started on 31December 2015. The objectives of AEC were to integrate diversity ofAsean economy into a single market with 625 million people ofinhabitant. AEC is expected to be a new market force in Asean andimprove economic development of Asean member countries. AEC willallow a free movement of goods and services, skilled labors and flow ofcapital in Asean countries. However, implementation of the AECframework is not an easy task; Trade policies, mobility of workers,diversity on politic, social, and economy including rapid growth ofeconomic development in China are some challenges to fully integrateAsean countries in a single market of AEC. For Indonesia, AEC providesopportunities to enhance export of goods and services in Aseancountries. Therefore competitiveness of Indonesian products in the AECmarket should be improved. Based upon components of competitivessreported by World Economic Forum (2014), Indonesia was in the top 5among Asean member countries, except competitiveness on efficiency inlabor market that was in the lowest position.